THE EFFECTS OF VALUE CREATION MODEL AND EXCELLENT SERVICES ON THE UPI IMAGE AND COMPETITIVENESS TOWARDS A RESEARCH-BASED TEACHING UNIVERSITY - Hurriyati, Ratih (International Journal of Education, 2014)
The Law Number 12 of 2012 concerning Higher Education (UUPT) stipulates that all State-Owned Legal Entity Universities (PT-BHMN) to be changed into Legal Entity State University (PTN-BH). The change provides opportunities to seven PT-BHMNs to design new statutes. The model of PTN-BH is similar to PT-BHMN, except that PTN BH’s financial system must follow the regulations set by Public Service Body (BLU). Basically, it is a strategic policy, although complex problems often arise in its implementation. With its PT-PKBLU status, UPI has not yet met the criteria of self-directing, self-motivating, self-regulating, self-supporting, self-assessing, and self-decision making in order to respond to challenging situations, as the regulation is rigid and set forth by government. The problem lies in how to put UPI in its role and position as PT-PKBLU effectively and efficiently while also being accountable and competitive. This is not easy. It takes a paradigm change and unconventional managerial strategy. Today, the number of private universities is increasing and each of them offers advantages. UPI must always be ready to compete with other universities, both private and state universities. However, compared to other state-owned universities, UPI is still left behind. Therefore, this research will focus on UPI’s competitiveness. To find out how UPI can improve its competitiveness to be a research-based teaching university, the writer is going to focus on a value creation model, excellent services, and UPI’s image which influence the improvement and enhancement of competitiveness. The units of analysis of the research were graduate students from 40 departments at UPI. To fid out the influence of each proposed indicator, the research employed SEM analysis, in which each variable was tested by a measurement model. The results show that a value creation model, superior services, institution’s image, and UPI’s competitiveness can lead UPI to be a research-based teaching university.